Dynamic impact mechanical damage analysis and tomato robotic post-picking crating optimization based on multiscale finite element model - Guohang Lu; Zinuo Wang; Nianzu Dai; Jin Yuan; Xuemei Liu; Georgios Papadakis (Smart Agricultural Technology)
Efficiency of harvesting robots remains a major bottleneck for increasing productivity, and the usual approach is to improve the parallelism between fruit separation and fruit crating. However, during robotic harvesting, achieving continuous and efficient fruit crating with low damage after fruit separation still needs to be urgently addressed, which is often overlooked but it is critical for maintaining fruit quality and harvesting efficiency. This study focuses on the dynamic mechanical damage analysis and optimization of a double-buffered post-picking crating process based on multiscale finite element model of tomatoes. First, by comparing the Burgers model and Multiscale Finite Element (MSFE) model, a framework for evaluating and optimizing tomato mechanical damage is presented. Then, the dynamic impacts and deformations of tomatoes during crating were simulated using the MSFE model, and critical damage thresholds were determined. A double-buffered cushioning system is introduced into the design of the tomato crating unit to constrain the impact velocities that may cause mechanical damage to the tomatoes. Based on the MSFE model and Response Surface Methodology (RSM), the double-buffered cushioning structure was optimized for efficient picking, low-damage crating process, and the crating process was validated with a customized test bench. Simulation tests the crating process determined safe impact velocities for tomato-to-tomato and tomato-to-container impacts, with maximum thresholds of 1530 mm/s and 911 mm/s, respectively. The optimal crating scheme with a primary buffer height of 40 mm, a secondary buffer angle of 30°, and the use of silicone pads as a cushioning material resulted in impact velocities of 1446.2 mm/s between the tomatoes at average mass and 676.45 mm/s with the container, which is well below the damage threshold. The results of the prototype tests showed that when fed at one per second, the damage rate of tomatoes was significantly reduced, the damage rate of only 2 %, and the mean crating time for tomatoes was 1.82 s which meets the robotic picking efficiency and low-damage requirements.